Postcard of J. L. Moreno - Moreno, J. L. (Jacob Levy), 1889-1974.
Postcard bearing Moreno's autograph, addressed to Mark Minguillon. The card features a photograph of Moreno and a printed version of his poem, Definition of the Encounter.
Psychiatrist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Minguillon, Mark -- Correspondence; Psychiatrists